2007
DOI: 10.1590/s0103-90162007000500011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of carbon and nitrogen determination methods for samples of a Paleudult subjected to no-till cropping systems

Abstract: Organic carbon (C) concentration evaluated by the Walkley-Black method, and total nitrogen (N) concentration determined by Kjeldahl method, were compared with corresponding results of C and N concentrations obtained through the dry combustion method (Elementar Vario EL analyzer), using samples of ten soil layers down to the depth of 107.5 cm of a kaolinitic Typic Paleudult (220-418 g clay kg -1 along the profile) subjected to no-till cropping systems [fallow bare soil, pigeon pea (Cajanus cajan L. Millsp.) plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 8 publications
3
17
0
Order By: Relevance
“…Nevertheless, it is the most widely used method in many laboratories because it is simple, rapid and less expensive and requires minimal equipment. Strong correlation is also found between these two methods regardless of agroecological region, land uses, cropping systems and managements (Dieckow et al ., ; Tivet et al ., ). For soils of the Indian NEHR, the Walkley and Black method has been an acceptable analytical technique to generate SOC data by weight to volume (Bhattacharyya et al ., ).…”
Section: Methodsmentioning
confidence: 96%
“…Nevertheless, it is the most widely used method in many laboratories because it is simple, rapid and less expensive and requires minimal equipment. Strong correlation is also found between these two methods regardless of agroecological region, land uses, cropping systems and managements (Dieckow et al ., ; Tivet et al ., ). For soils of the Indian NEHR, the Walkley and Black method has been an acceptable analytical technique to generate SOC data by weight to volume (Bhattacharyya et al ., ).…”
Section: Methodsmentioning
confidence: 96%
“…The effect of crop rotation in increasing C stocks, in this soil layer, was probably linked to the cover crop root system. Previously, Dieckow et al (2007) reported that 36 and 63 % of the gain in soil C stocks associated to the use of pigeon pea (Cajanus cajan (L.) Milsp. )/maize and lablab bean (Dolichos lablab L.)/maize, respectively, occurred below 0.175 m depth.…”
Section: Carbon Stocks In Stratified Soil Layersmentioning
confidence: 99%
“…Indeed, this factor of conversion, which is quite variable (1.35 to 14.1; [54]), has been shown to vary with soil type, mineralogy and soil depth [55,56]. Similarly, dry combustion processes have also resulted in greater N values than the Kjeldahl method [57,58]. Thus, considering this limitation, we were unable to test for the effect of time on soil C, N and CN ratios.…”
Section: Discussionmentioning
confidence: 98%